ATMOSPHERIC CONDITIONS REFLECTED IN CHEMICAL COMPONENTS IN SNOW OVER EAST QUEEN MAUD LAND, ANTARCTICA - カミヤマ, コキチ; ワタナベ, オキツグ; ナカヤマ, エイイチロウ; KAMIYAMA, Kokichi; WATANABE, Okitsugu; NAKAYAMA, Eiichiro (National Institute of Polar Research, 1992)
P(論文) The precise vertical distribution of H_2O_2 in the surface snow layer at three different sites in the inland region of Antarctica was measured. The seasonal variation, traced from the vertical distribution of snow cover, reflects photochemical processes in the atmosphere and coincides with that of δ^<18>O. The values of pH and the concentration of micro-particles are also discussed in consideration of photochemical and migration processes in the atmosphere. Almost all substances occurring in snow have unique origins; some of them reflect physical and chemical processes in the atmosphere. departmental bulletin paper